1970
DOI: 10.1111/j.1528-1157.1970.tb03888.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paroxysmal Spike‐Wave on Continuous Visual‐Motor Performance

Abstract: a few had been referred to the Department of Neurology of the University of Virginia. All patients were having clinical absence attacks with generalized spike-wave activity during routine electroencephalography. Most of the patients had several electroencephalograms and none revealed focal discharge. They were 7-19 years old, and none was retarded. One child, for whom no IQ score was available, was thought to have borderline subnormal intelligence but he had no difficulty with the pursuit-rotor task.A photoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
2

Year Published

1976
1976
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(50 citation statements)
references
References 13 publications
3
45
0
2
Order By: Relevance
“…This study, however, must be interpreted with caution for several reasons: (1) 15 of their 25 patients were mentally retarded; (2) the patients were receiving other drugs at the time of the trial; (3) they did not include a control group for comparison. The importance of proper controls in such a study as this is paramount, especially as it has been shown that EEG spike/wave activity of petit mal epilepsy may be correlated with impaired visual-motor performance (Goode et al, 1970). An important feature that the study again emphasizes, however, is the necessity to explore as many individual components of intellectual functioning as possible.…”
Section: Ethosuximidementioning
confidence: 99%
“…This study, however, must be interpreted with caution for several reasons: (1) 15 of their 25 patients were mentally retarded; (2) the patients were receiving other drugs at the time of the trial; (3) they did not include a control group for comparison. The importance of proper controls in such a study as this is paramount, especially as it has been shown that EEG spike/wave activity of petit mal epilepsy may be correlated with impaired visual-motor performance (Goode et al, 1970). An important feature that the study again emphasizes, however, is the necessity to explore as many individual components of intellectual functioning as possible.…”
Section: Ethosuximidementioning
confidence: 99%
“…Por vezes, essas descargas apareceram entre uma resposta e o estímulo seguinte, o u seja, em momento inadequado para a análise. Provavelmente houve inibição das descargas nas atividades cognitivas, fato também relatado em outras séries de pacientes com AE generalizada 21,23 . É possível que a utilização, em cada paciente, de testes mais variados e de diferentes níveis de dificuldade, pudesse identificar os que ocasionassem menor redução de AE 2 5 .…”
Section: Discussionunclassified
“…Recentemente tem sido mostrada a redução da AE com algumas drogas antiepilépticas 1 7 , 1 8 , o que tem trazido benefícios cognitivos aos pacientes, em certas condições clínicas 18,19 . As pesquisas sobre DCT são ainda pouco num e rosas e apresentam limitações em vários aspectos, como o número de indivíduos, distinção entre DCT e crise evidente e o tipo de casuística estudada 6,20,21 , O objetivo desta pesquisa é estudar a ocorr ê ncia de DCT associado a AE generalizada ou difusa com a aplicação de vários testes cognitivos.…”
unclassified
“…It has been suggested that this phenomenon is due the spreading of pathological electrophysiological discharges to the frontal networks involved in attentional control [33,75]. Thus individuals undergoing limbic status epilepticus may be somewhat aware of their environment, but are focusing their attention on the vivid experiential phenomena induced by the electrical stimulation of the temporal lobe [31].…”
Section: Epileptic Seizuresmentioning
confidence: 99%